2022
DOI: 10.3389/fmicb.2022.1060947
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas13a system: A novel tool for molecular diagnostics

Abstract: The clustered regularly interspaced short palindromic repeats (CRISPR) system is a natural adaptive immune system of prokaryotes. The CRISPR-Cas system is currently divided into two classes and six types: types I, III, and IV in class 1 systems and types II, V, and VI in class 2 systems. Among the CRISPR-Cas type VI systems, the CRISPR/Cas13a system has been the most widely characterized for its application in molecular diagnostics, gene therapy, gene editing, and RNA imaging. Moreover, because of the trans-cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 119 publications
0
28
0
Order By: Relevance
“…CRISPR/Cas13a system consists of Cas13a protein and single crRNA. Cas13a protein has two types of RNAase activity, one for pre-crRNA processing to promote the formation of ribonucleoprotein complexes (RNPs), and the other for cis-cleavage of targeted RNA or trans-cleavage of nonspecific RNA (Zhao, Qiu, et al, 2022). When the complexes of Cas13a and crRNA bind to the targeted single-stranded RNA, the conformational change of the RNP complex is triggered to cleave targeted site and results in the editing and regulation at the RNA level.…”
Section: Crispr/cas13a Systemmentioning
confidence: 99%
“…CRISPR/Cas13a system consists of Cas13a protein and single crRNA. Cas13a protein has two types of RNAase activity, one for pre-crRNA processing to promote the formation of ribonucleoprotein complexes (RNPs), and the other for cis-cleavage of targeted RNA or trans-cleavage of nonspecific RNA (Zhao, Qiu, et al, 2022). When the complexes of Cas13a and crRNA bind to the targeted single-stranded RNA, the conformational change of the RNP complex is triggered to cleave targeted site and results in the editing and regulation at the RNA level.…”
Section: Crispr/cas13a Systemmentioning
confidence: 99%
“…1d), which tends to cleave at uracil or adenine bases and possesses target-dependent single-stranded RNA trans -cleavage activity. 69 Cas13a also possesses a distinctive feature: once it recognizes and cleaves the RNA target specified by the crRNA sequence, it transitions into an enzymatic “activated” state. In this state, it binds to and cleaves other RNAs, regardless of their homology with the crRNA or the presence of a PFS.…”
Section: Crispr/cas Systemsmentioning
confidence: 99%
“…Cas13 in type VI targets single-stranded RNA and is the first Cas protein discovered to recognize RNA specifically [ 37 ], with the ability to cleave ssRNA in both cis and trans orientations. Cas13a (C2c2), Cas13b, Cas13c, and Cas13d make up the majority of the Cas13 family [ 38 , 39 , 40 , 41 ]. Further investigation revealed that the system does not require tracrRNA, but rather a protospacer flanking site (PFS) similar to PAM that has an “adjunct cleavage effect” on RNA [ 11 ].…”
Section: Classification and Characterization Of Crispr Systemsmentioning
confidence: 99%